Dimensi Eko-Eskatologis dalam Mitos Penciptaan pada Masyarakat Manggarai Nusa Tenggara Timur - Sefrianus Juhani; Antonius Denny Firmanto (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2021)
One of the problems suspected to be faced by human is environmental problems. Whereas in various traditions generated by the ancestors, it encourages harmony between human life and nature through mythology, including the teachings of eschatology. The ecological crisis that occurred because of leaving the concept of eco-eschatology in religion and culture. This paper aims to find the ecoeschatological dimension in the creation myth of the Manggarai Community, NTT. The study used qualitative approach with ethnographic methods. Data were obtained through interviews with several key informants from several villages in Manggarai. The results of the study found two myths that have the eco-eschatological  local wisdom, namely the myth of the origin of humans and the origin of plants. There are several eco-eschatological meanings in the creation myth, those are everything was created by Morin, all creations have an eschatological future, and there is continuity and discontinuity between the old creation in the world and the new creation in the eschatological world. These meanings bear some resemblance to the teachings in Catholic theology of creation. This finding contributes to the Church in efforts to sensitize the people in relation to the ecological crisis. In addition, local wisdom is also the basis for the environmental conservation movement.